FLORA OF UNITED STATES OF AMERICA AND NEIGHBORING NORTH AMERICAN COUNTRIES IN POLTAVA STATE AGRARIAN ACADEMY’S ARBORETUM - Колесніков, Л. О.; Колеснікова, О. Л. (Scientific Progress & Innovations, 2013)
Distribution by geographic prevalence was made after the ecological-geographical analysis of dendroflora in Poltava State Agrarian Academy’s park. Completed: generic analysis - the distribution of flora by geographical origin and history of settlement criteria, botanical and geographical analysis – establishing links of arboretum flora with other flora. Highlighted the plants that come from the North American region. Shown the environmental standard for plants: edaphic requirements, conditions of light, temperature, phytopathological stability. Ecological- phytocoenosis analysis was mate for distribution of flora in conditions of growth.